2019
DOI: 10.1038/s41598-019-42062-8
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of the freeze-dried mouse sperm nucleus to temperatures ranging from −196 °C to 150 °C

Abstract: It has long been believed that tolerance against extreme environments is possible only for ‘lower’ groups, such as archaea, bacteria or tardigrades, and not for more ‘advanced’ species. Here, we demonstrated that the mammalian sperm nucleus also exhibited strong tolerance to cold and hot temperatures. When mouse spermatozoa were freeze-dried (FD), similar to the anhydrobiosis of Tardigrades, all spermatozoa were ostensibly dead after rehydration. However, offspring were obtained from recovered FD sperm nuclei,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
1
23
0
Order By: Relevance
“…1e, 2c, d; Table 4). Very recently, we reported that trehalose could increase the tolerance of FD sperm against extremely high temperatures by protecting FD sperm from burning [15]. Those results suggest that trehalose has the potential to protect several factors (such as the integrity of acrosome or cytoplasm) of FD sperm but not DNA, and therefore, even though the birth rate was increased, DNA damage was not reduced by trehalose treatment.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…1e, 2c, d; Table 4). Very recently, we reported that trehalose could increase the tolerance of FD sperm against extremely high temperatures by protecting FD sperm from burning [15]. Those results suggest that trehalose has the potential to protect several factors (such as the integrity of acrosome or cytoplasm) of FD sperm but not DNA, and therefore, even though the birth rate was increased, DNA damage was not reduced by trehalose treatment.…”
Section: Discussionmentioning
confidence: 95%
“…However, the gametes of inbred mouse strains are sensitive to assisted reproductive technology, and the production rate of offspring from inbred strains was reported to be lower than that of hybrid strains [9, 33]. Because DNA was common in all organisms, those differences were likely caused by the tolerance of the cell membrane or some organelle rather than the DNA [15, 34]. Therefore, trehalose could work more effectively in the “weaker” spermatozoa of inbred strains compared with the “stronger” spermatozoa of outbred or hybrid strains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These cryoprotectants remain liquid, and toxic, at room temperature and are therefore unsuitable for use in dry storage. Consequently, scientists started investigating solutions to this problem using milder cold temperatures to solidify water prior to sublimation (Restrepo et al 2019;Wakayama et al 2019;Palazzese et al 2020) with better results. After all, the aforementioned anhydrobiotes do not resort to freezing before dehydration; simply put, once a reduction in environmental water is sensed, they activate a timely, regulated gene expression leading to the accumulation of xeroprotectants in their cells.…”
Section: Somatic Cells: Current Situationmentioning
confidence: 99%
“…The lyophilization method allows storage of sperm at 4°C or room temperature for a long time, does not require regular replenishment of a freezing agent, and is relatively easy to manage. Mouse spermatozoa after freeze-drying can be stored at room temperature for more than one year [5], and can withstand rapid temperature change [6]. In addition, sperm processed by the lyophilization method can withstand storage in space, which is a high radiation environment [7].…”
Section: Lyophilization (Freeze-drying)mentioning
confidence: 99%